Snares: Pere Gimferrer's Los espejos/ Els miralls - Margaret Persin (Studies in 20th & 21st Century Literature, 1992)
With the publication of Els miralls, Pere Gimferrer effected a major shift in philosophical and linguistic perspective. It is the first collection to be published in Catalan, and thus represents for the well-known writer a change in direction for him as a poet and spokesperson of his culture and his generation. But the change is more than one of mere language coding. For in this collection, the Catalan poet confronts all the snares of language which he views as limiting of creativity and originality. He adopts a variety of poetic strategies and voices in an attempt to come to terms with a view of language that will acknowledge its wiles, deceptions and imperfect reflections. Ironically, the power of this collection derives from the decentering of authorial voice, the breaking of limits and the questioning stance that is communicated in regard to language as a closed system of signification.
Keywords: Els miralls; Pere Gimferrer; philosophy; Catalan; linguistic perspective; culture; language; language coding; poetic strategy; sign